Multifaceted Assessment of Chronic Gastritis: A Study of Correlations between Serological, Endoscopic, and Histological Diagnostics - Toshitatsu Takao; Takeshi Ishikawa; Takashi Ando; Madoka Takao; Tsuguhiro Matsumoto; Yutaka Isozaki; Mika Okita; Yasuyuki Nagao; Hirokazu Oyamada; Keiichi Yokoyama; Atsushi Tatebe; Kazuhiko Uchiyama; et al. (Gastroenterology Research and Practice)
Aim. Chronic gastritis was assessed serologically, endoscopically and histologically to identify correlations between these methods. Methods. Subjects comprised 319 patients who had provided informed consent. Serological assessment of chronic gastritis was based on the pepsinogen test method. Endoscopic gastritis and histological gastritis were assessed and scored according to the Kimura-Takemoto classification system and the updated Sydney classification system respectively, and correlations between these three methods were studied. Results. Pepsinogen I/II ratio showed a significant correlation to the extent of mononuclear cell infiltration of the gastric corpus. When histological gastritis was divided, on the basis of the distribution of mononuclear cell infiltration, into gastritis limited to the antrum and corpus gastritis, these types were distinguished with high accuracy using a pepsinogen I/II ratio of 3 as the cutoff. A good correlation was also seen between pepsinogen I/II ratio and development of atrophy in endoscopic gastritis, where groups with and without advanced atrophy were also distinguished with high accuracy using a cutoff value of 3. Conclusion. Significant correlations exist between serum pepsinogen levels, endoscopic gastritis, and histological gastritis. Pepsinogen I/II ratio allows prediction of the existence of endoscopic gastritis and histological gastritis, or the extent of their development, with high accuracy.